Progression characteristics of ellipsoid zone loss in macular telangiectasia type 2. Issue 7 (9th April 2019) - Pauleikhoff, Daniel; Bonelli, Roberto; Dubis, Adam M; Gunnemann, Frederic; Rothaus, Kai; Charbel Issa, Peter; Heeren, Tjebo FC; Peto, Tunde; Clemons, Traci E; Chew, Emily Y; Bird, Alan C; Sallo, Ferenc B; et al.
Abstract: Purpose: To investigate the progression characteristics of ellipsoid zone (EZ) loss in eyes with macular telangiectasia type 2 (MacTel) as reflected by area and linear measurements, and their relevance for visual acuity. Methods: Participants were selected from the MacTel Study cohort. Linear and area measurements of EZ loss were performed in Spectral‐Domain Optical Coherence Tomograph (SD‐OCT) volume scans. Progression characteristics and correlations between linear and area measurements were analysed using linear mixed effects models. Results: A total of 134 eyes of 70 patients were included (85 eyes with follow‐up, mean 4.7 years, range: 1.4–8 years). Ellipsoid zone (EZ) loss significantly progressed at a mean annual increment of 0.057 mm 2 (p = 0.005). The progression rate was non‐linear and interacted significantly with initial EZ lesion size indicating an exponential growth before reaching a plateau. There was a strong heterogeneity in area sizes between fellow eyes. EZ break length had a significant linear effect on EZ break area ( b  = 1.06, p < 0.001) and could predict it. The location of the EZ break had a significant impact on visual acuity. Conclusion: Ellipsoid zone (EZ) loss in MacTel has a non‐linear progression characteristic, and its rate depends on area size at baseline, which must be taken into account at sample selection in clinical trials. Our results show a good correlation of linear and area measures of EZ loss and a segregation of best‐corrected visual acuity by EZ location, which may help routine clinical practice.